Perioperative Anesthesia and Acute Smell Alterations in Spine Surgery: A “Sniffing Impairment” Influencing Refeeding? - Briguglio, Matteo; Crespi, Tiziano; Langella, Francesco; Riso, Patrizia; Porrini, Marisa; Scaramuzzo, Laura; Bassani, Roberto; Brayda-Bruno, Marco; Berjano, Pedro (Frontiers in Surgery, 2022)
Medications for general anesthesia can cause smell alterations after surgery, with inhalation anesthetics being the most acknowledged drugs. However, spine patients have been poorly studied in past investigations and whether these alterations could influence the refeeding remains unclear. This research aims to observe detectable dysosmias after spine surgery, to explore any amplified affection of halogenates (DESflurane and SEVoflurane) against total intravenous anesthesia (TIVA), and to spot potential repercussions on the refeeding. Fifty patients between 50 and 85 years old were recruited before elective spine procedure and tested for odor acuity and discrimination using the Sniffin’ Sticks test. The odor abilities were re-assessed within the first 15 hours after surgery together with the monitoring of food intakes. The threshold reduced from 4.92 ± 1.61 to 4.81 ± 1.64 (p=0.237) and the discrimination ability reduced from 10.50 ± 1.83 to 9.52 ± 1.98 (p=0.0005). Anesthetic-specific analysis showed a significant reduction of both threshold (p=0.004) and discrimination (p=0.004) in the SEV group, and a significant reduction of discrimination abilities (p=0.016) in the DES group. No dysosmias were observed in TIVA patients after surgery. Food intakes were lower in the TIVA group compared to both DES (p=0.026) and SEV (p=0.017). The food consumed was not associated with the sniffing impairment but appeared to be inversely associated with the surgical time. These results confirmed the evidence on inhalation anesthetics to cause smell alterations in spine patients. Furthermore, the poor early oral intake after complex procedures suggests that spinal deformity surgery could be a practical challenge to early oral nutrition.